2021
DOI: 10.1038/s41598-021-89774-4
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic zone detection in MRI negative epilepsy using adaptive thresholding of arterial spin labeling data

Abstract: Drug-resistant epilepsy is a diagnostic and therapeutic challenge, mainly in patients with negative MRI findings. State-of-the-art imaging methods complement standard epilepsy protocols with new information and help epileptologists to increase the reliability of their decisions. In this study, we investigate whether arterial spin labeling (ASL) perfusion MRI can help localize the epileptogenic zone (EZ). To that end, we developed an image processing method to detect the EZ as an area with hypoperfusion relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…ASL is an MRI perfusion technique that enables the quantification of cerebral blood flow. Recent studies demonstrated a high efficacy of ASL 19 and similar results of PET and ASL in localizing EZ in MR negative epilepsy 20 . The important advantage of ASL over FDG-PET is its independence from the application of a radioactive tracer, rapid data acquisition within the spectrum of clinical MR recorded in epilepsy patients, and lower costs 35 .…”
Section: Discussionmentioning
confidence: 82%
“…ASL is an MRI perfusion technique that enables the quantification of cerebral blood flow. Recent studies demonstrated a high efficacy of ASL 19 and similar results of PET and ASL in localizing EZ in MR negative epilepsy 20 . The important advantage of ASL over FDG-PET is its independence from the application of a radioactive tracer, rapid data acquisition within the spectrum of clinical MR recorded in epilepsy patients, and lower costs 35 .…”
Section: Discussionmentioning
confidence: 82%
“…Виявлення можливих структурних змін у головному мозку шляхом застосування методів нейровізуалізації є обов'язковим діагностичним методом під час обстеження дитини з ЕЕ або епілептиформними та розвитковими енцефалопатіями (ЕРЕ), який дозволяє виявити потенційно епілептогенні вогнища та, у багатьох випадках, верифікувати етіологію захворювання. Однак, у 20-50% дітей із рефрактерними до терапії нападами під час проведення МРТ головного мозку, навіть із використанням оптимального протоколу, структурні зміни в мозку не ідентифікуються, що ускладнює подальший діагностичний пошук та може вимагати проведення додаткових методів нейровізуалізації [5,12,26,27].…”
Section: вступunclassified
“…In animals, brain ASL-MRI has been used widely in experimental research ( 67–71 ). Recently, Hoffman et al successfully performed ASL in a large population of dogs and cats with a success rate of 95% in animals with a normal brain MRI.…”
Section: Techniquesmentioning
confidence: 99%